MANAGEMENT OF PULMONARY PARACOCCIDIOIDOMYCOSIS: AN INTEGRATIVE REVIEW - Brito, Carla Maria Soares; Lopes, Lúcio Eugênio Cerqueira; Lira, Elton Jones Dias; Barros, Gullit Vinicius Silva; Brito, João Felipe Fernandes; Lima, Maria Tereza Viana; Pinheiro, Judimilla Almeida; Fortes, Marina Sampaio; Carvalho, João Lucas Gomes; Sousa, Iargo Franco Diogenes Urbano; de Carvalho, Gabriel Guedes Farias; Daboit, Tatiane Caroline (Seven Editora, 2025)
The present study aims to describe the clinical management of pulmonary paracoccidioidomycosis through the literature. The study used as a method the integrative literature review, carried out via the Virtual Health Library (VHL), and through a search in the Medline, Pubmed and Scielo (Scientific Electronic Library Online) databases using the descriptors "Paracoccidioidomycosis", "Diagnosis".  For the evaluation of the research problem and its stratification, the PVO strategy was used, and the following strategy was formulated, which can be seen in Chart 1.  The aforementioned strategy allowed the following guiding question to be formulated: What is the importance of diagnosing and treating pulmonary paracoccidioidomycosis (PCM)? The standard diagnosis of PCM is visualization in clinical specimens by direct examination or histopathology of characteristic cells with multiple buttons in biological fluids or fungal isolation. As the choice of the drug to be used depends on the clinical form of the disease, clinical follow-up of the patients being treated is necessary and, if it is necessary to adjust the dose of the drug, side effects may also arise, making it necessary to switch to another drug. Finally, even with clinical improvement throughout the treatment, it is necessary to monitor the patient accurately to avoid recurrence of the disease. Fungal diseases in general and especially paracoccidiodomycosis are a public health problem in Latin America.DOI: https://doi.org/10.56238/sevened2024.037-150